Kajian Kodikologis atas Surat Sultan Kanoman, Cirebon (COD. OR. 2241 ILLB 17 (No. 80)) - Pudjiastuti, Titik (UI Scholars Hub, 2007)
In the Universitets-Bibliotheek (UB) Leiden there is a pile of Banten letters that are bundled in Cod.Or. 2241 Illb. The 17th (No. 80) letter is a letter from Sultan Anom to the Governour General Willem Arnold Alting and Raad van Indie in Batavia. The content of the letter, which is undated and written in Javanese hanacaraka, is an approval of Sultan given to Raad van Indie for the building of a new house in Indramayu. Based on the codicological analysis of the shape, kind of paper, seal, scripts, and the language, it can be concluded that those letters in the budle were in fact not sent form Sultan Anom of Banten but form Sultan Kanoman of Cirebon.